Should National Happiness be Maximized? - Bruno S. Frey; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2007)
Cross-disciplinary ?happiness research? has made big progress in the measurement of individual welfare. This development makes it tempting to pursue the old dream of maximizing aggregate happiness as a social welfare function. However, we postulate that the appropriate approach is not to maximize aggregate happiness in seeking to improve outcomes by direct policy interventions. The goal of happiness research should rather be to improve the nature of the processes through which individuals can express their preferences. Individuals should become better able to advance their idea of the good life, both individually and collectively.
Keywords: D60; D70; H11; I31; 330; Economic policy; happiness; life satisfaction; political economy; social welfare; utility